2020
DOI: 10.1038/s41598-020-60966-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chloromethylisothiazolinone/methylisothiazolinone (CMIT/MIT) on Th2/Th17-related immune modulation in an atopic dermatitis mouse model

Abstract: Exposure to chloromethylisothiazolinone/methylisothiazolinone (CMIT/MIT) has been associated with allergic contact dermatitis and occupational asthma. Despite this association however, no study has investigated the effects of CMIT/MIT exposure on the development of atopic dermatitis (AD). This study was conducted to investigate the influence of epicutaneous exposure to CMIT/MIT on AD in a mouse model and the underlying biological mechanisms. BALB/C mice were exposed to CMIT/MIT for 3 weeks and AD was developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 61 publications
(71 reference statements)
0
11
0
1
Order By: Relevance
“…Topical treatment with APR-ME on the inflamed area significantly reduced the expression of these cytokines. The role of IL-8, IL-17A and TNFα in skin inflammation has been widely described in previous studies [ 67 , 68 , 69 ]. TNF-α is a multifunctional agent that stimulates the acute phase of an inflammatory reaction and is secreted by different cell types, including monocytes, macrophages, Langerhans cells and microglia [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Topical treatment with APR-ME on the inflamed area significantly reduced the expression of these cytokines. The role of IL-8, IL-17A and TNFα in skin inflammation has been widely described in previous studies [ 67 , 68 , 69 ]. TNF-α is a multifunctional agent that stimulates the acute phase of an inflammatory reaction and is secreted by different cell types, including monocytes, macrophages, Langerhans cells and microglia [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, among the models evaluated for this study, six murine models demonstrated broad upregulation of Th1, Th2, Th17, and Th22 inflammation: Adam17 fl/fl Sox9 Cre , IL-23-exposed, OXA-induced, OVA-induced, ft, and vitamin D3-induced mice. OVA with CMIT/MIT exposure, ft mice, and HDM-induced mice [28,[36][37][38]. While ovalbumin commonly to induce eczema in mice, Go et al (2020), found that mice sensitized with CMIT/MIT before OVA displayed an augmented Th17 reaction than mice exposed to OVA alone [36].…”
Section: An Overview Of Mouse Models For Atopic Dermatitismentioning
confidence: 99%
“…It was found that Thl7 and Tregs cells were also significantly related to the pathogenesis of asthma [51][52][53]. Synergy of multiple pathways, such as Th2, Th17, and even eosinophil/neutrophil infiltration, has been found in some asthma models [54][55][56]. The view that eosinophilic asthma is an exclusive TH2 disorder and neutrophil asthma is an exclusive TH17 disorder may be oversimplified [57].…”
Section: Adjusting Thl7/tregs Balancementioning
confidence: 99%